2016
DOI: 10.1007/978-3-319-32374-9_11-1
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Disease Management

Abstract: Pre-and postharvest disease control for ornamental plants is mainly provided via fungicide or bactericide application. However, disease control with conventional chemical compounds carries the risk of resistance development by new pathogen races. Additionally, there is increasing public concern over fungicide usage in terms of human and environmental risk. For this reason, and over the past 20 years, researchers developed novel postharvest disease management strategies for cut flowers and other ornamentals. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…Bent-neck symptoms occur when the floral xylem is attacked by bacteria or fungi, which block water uptake, resulting in a short flower vase life [92,97]. As indicated in previous studies, the number of bacteria and fungi in the vase water is related to the vase life of cut flowers [47,55,98,99]. The hydraulic conductivity of flower stems decreases with the number of bacteria per cut flower stem fresh weight [100][101][102].…”
Section: Germicides or Biocidesmentioning
confidence: 78%
“…Bent-neck symptoms occur when the floral xylem is attacked by bacteria or fungi, which block water uptake, resulting in a short flower vase life [92,97]. As indicated in previous studies, the number of bacteria and fungi in the vase water is related to the vase life of cut flowers [47,55,98,99]. The hydraulic conductivity of flower stems decreases with the number of bacteria per cut flower stem fresh weight [100][101][102].…”
Section: Germicides or Biocidesmentioning
confidence: 78%
“…In the past 50 years, research on the biological control of pests and diseases has shown that within the complex host-pathogen, host-pest interactions, biological agents may provide alternative solutions for IPDM [56][57][58]. Host-pathogen interactions include antibiosis, antagonism for space and nutrients, induction of the host's defense responses, and many more [58][59][60]. Microbes that provide antagonism may restrict plant pathogens by up to 100% in vitro.…”
Section: Integrated Pest and Disease Management (Ipdm)mentioning
confidence: 99%
“…This was associated with the environment conditions, which significantly affect both the pathogen and the biological agent. In addition, abiotic elicitor treatments such as acibenzolar-S-methyl (ASM), methyl jasmonate (MeJA), and ultraviolet-C (UV-C) irradiation, as alternatives to fungicides, have been used to induce defense responses in cut flower and pot plant cultivation [58,61].…”
Section: Integrated Pest and Disease Management (Ipdm)mentioning
confidence: 99%
“…The most common diseases caused by plant pathogenic fungi are anthracnose, blight, canker, damping off, dieback, gall, leaf spot, powdery mildew, rust, root rot, scab, and wilt ( Iqbal et al., 2018 ; Hussain and Usman, 2019 ; Jain et al., 2019 ). These diseases can generate significant losses in yield ( Godfray et al., 2016 ), quality and quantity ( Shuping and Eloff, 2017 ) in various agricultural systems ( Rodriguez-Moreno et al., 2018 ) of economically important agronomical ( Leonard and Szabo, 2005 ; Asibi et al., 2019 ), horticultural ( Agrios, 2009 ; Wenneker and Thomma, 2020 ), floricultural and ornamental ( Darras, 2016 ; Lecomte et al., 2016 ), and forest ( Ritz, 2005 ; Marčiulynas et al., 2020 ) plant species worldwide ( Malcolm et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%